MENGUNGKAP FAKTA FAKTOR RISIKO DIABETES MELITUS DI INDONESIA - Azriful Azriful; Yudi Adnan; Emmi Bujawati; Syamsul Alam; Nildawati Nildawati (Media Penelitian dan Pengembangan Kesehatan, 2024)
The increase in the prevalence of diabetes mellitus in Indonesia is influenced by the interaction of internal and external multifactors. The incidence of DM is predicted to continue to increase to reach 578 million in 2030 and 700 million in 2045. This study aimed to analyze factors related to the incidence of diabetes in Indonesia.  This research used quantitative methods with a cross sectional approach and uses secondary data taken from the source "Riskesdas 2018". The unit of analysis in this research is 34 provinces in Indonesia. Data was analyzed using scatter plot diagrams. The results of the study showed that smoking habits, lack of physical activity, obesity, and difficulty in accessing primary health care have been shown to contribute to an increased risk of diabetes mellitus. Meanwhile, consumption of sweet foods is not directly related to an increase in diabetes mellitus. Health campaigns targeting smoking behavior, promotion of active lifestyles, education about the dangers of obesity, and improving the accessibility of health services can help reduce the risk of diabetes. Further research is needed to understand more deeply the factors that may contribute to the relationship between consumption of sweet foods that are not directly related to increased diabetes mellitus, as well as to design more effective intervention strategies.